2016
DOI: 10.1371/journal.pone.0165681
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of TMEM173 Predicts Poor Prognosis in Patients with Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal cancer types, and chronic infection with Hepatitis B Virus (HBV) is identified as the strongest risk factor for HCC. Transmembrane Protein 173 (TMEM173) is a pattern recognition receptor which functions as a major regulator of the innate immune response to viral and bacterial infections. However, the prognostic value of TMEM173 in HCC remains elusive. Thus, we aimed to evaluate the potential prognostic significance of TMEM173 expression in HCC patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…STING was reported to be frequently inactivated in HPV-induced cancers (110) and in a large portion of melanomas (111). Low expression of STING in hepatocellular carcinoma (HCC) tissues was closely related to more advanced tumor stages and a worse outcome (112). Low RIG-I expression led to shorter survival and poor prognosis of patients with HCC (113) and gastric cancer (114).…”
Section: Perspectives Of Hippo-yap -Innate Immunity Crosstalk In Tumomentioning
confidence: 99%
“…STING was reported to be frequently inactivated in HPV-induced cancers (110) and in a large portion of melanomas (111). Low expression of STING in hepatocellular carcinoma (HCC) tissues was closely related to more advanced tumor stages and a worse outcome (112). Low RIG-I expression led to shorter survival and poor prognosis of patients with HCC (113) and gastric cancer (114).…”
Section: Perspectives Of Hippo-yap -Innate Immunity Crosstalk In Tumomentioning
confidence: 99%
“…Clinical studies revealed that the expression of STING was significantly reduced in HCC tissues compared to the controls, and lower expression of STING was associated with a more advanced tumor stages and a worse survival ( 27 ) as well with poor prognosis for patients with gastric cancer ( 28 ). Collectively, these studies suggest that STING and RIG-I sensors may serve as tumor suppressors and have clinical values against certain types of tumors as prognostic/predictive biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Most genes showed remarkable features, which were highly upregulated in LFGC but down-regulated in HFGC ( Figure S14A-B, top panels), and showed negative association with FGC ( Figure S14A-B, bottom panels) in TIGER-LC. Furthermore, several genes expressed much higher in LFGC than those in HFGC (Figure S14C-D) have been reported to be involved in the development and progression of liver 1 2 cancer [29][30][31][32] . Also, we found that PDCD1LG2 (PD-L2), ligand for PD-1, was up-regulated in LFGC compared to HFGC indicative of the sensitivity to the immune-checkpoint inhibitor (ICI) 33 .…”
Section: (Supplementary Materials and Methods) Consistent With The Cmentioning
confidence: 99%